1998
DOI: 10.1111/j.1600-0536.1998.tb05765.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous reactivity of the hands in nickel‐sensitive patients with hand eczema

Abstract: This study compares the cutaneous reactivity between the hand and the back for 7 female patients with active hand eczema, who were found to be nickel-sensitive on routine patch testing with the European standard series. Patients were patch tested to a dilution series of nickel sulfate on the back in order to determine the threshold concentration for elicitation of allergic contact dermatitis, and based upon this result a lower concentration of nickel was then used for patch tests on the hand. We found that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
(8 reference statements)
1
19
0
Order By: Relevance
“…Hand eczema with nickel allergy turned out to have an especially bad prognosis (15), because even a small amount of nickel can induce clinical manifestations, and nickel containing materials are inevitable in our surroundings (9). Furthermore, patients with nickel allergy may have a skin barrier defect that does not exist in non‐allergy patients (8). Some studies have demonstrated that skin barrier disruption induces an increase in epidermal Langerhan's cell density accompanied by an enhanced response in allergic contact dermatitis (16) and that the disrupted barrier state in nickel‐mediated contact allergy was improved by application of a moisturizer (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand eczema with nickel allergy turned out to have an especially bad prognosis (15), because even a small amount of nickel can induce clinical manifestations, and nickel containing materials are inevitable in our surroundings (9). Furthermore, patients with nickel allergy may have a skin barrier defect that does not exist in non‐allergy patients (8). Some studies have demonstrated that skin barrier disruption induces an increase in epidermal Langerhan's cell density accompanied by an enhanced response in allergic contact dermatitis (16) and that the disrupted barrier state in nickel‐mediated contact allergy was improved by application of a moisturizer (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nickel is suspected as a cause of hand eczema. Furthermore, patients with a nickel allergy are known to have a worse prognosis than non‐allergic patients (8). Although the cause is not entirely clear, plausible explanations include the ability of nickel to induce clinical manifestations in even minute amounts and its nearly ubiquitous presence in our normal surroundings (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lidén et al showed that nickel was released from 1 and 2 euro coins in similar amounts and that nickel was deposited on the fingers and hands after 1 hr of handling (0.09–4.1 µg/cm 2 ) (150). The authors concluded that coin handling could play a role in nickel dermatitis (150) as it is known that a few patients may react to low nickel concentration on the hands (151). Although the euro coin debate has recently calmed down, several studies and letters have addressed this issue over the years (152, 153).…”
mentioning
confidence: 99%
“…A 15-μ L aliquot of each test solution was micropipetted onto a filter paper disc placed within a small, 8-mm Finn Chamber on Scanpor® (Epitest Ltd Oy, Tuusula, Finland). 23,24 The diagnostic test concentrations of 5.0% (50 000 ppm, pet.) nickel sulphate and 0.5% (5000 ppm, pet.)…”
Section: Test Proceduresmentioning
confidence: 99%